THE PRINCIPLE OF NON-REFOULEMENT IN THE PRACTICE OF THE CONSTITUTIONAL COURT OF SERBIA IN THE LIGHT OF GENERALLY RECOGNIZED RULES OF THE INTERNATIONAL LAW: FROM RECOGNITION TO THE LACK OF IMPLEMENTATION - Kovačević, Nikola (Pravni zapisi, 2020)
The absolute prohibition of torture and other forms of ill-treatment stands as one of the most fundamental values of democratic societies and represents the peremptory norm of international law. The respect of this prohibition implies non-refoulement – an obligation of the States to refrain from sending individuals back to the territory of the receiving countries where substantial grounds have been shown for believing that the person in question, if removed, would face ill-treatment. Taking into consideration that the jurisprudence of the European Court of Human Rights has significantly developed in the last two decades, the principle of non-refoulement has become one of the most exciting human rights topics worldwide. The Constitution of Serbia stipulates that the generally recognized rules of the international law form an integral part of Serbian legal system, including the rules of international customary law. Moreover, interpretation of the human rights provisions of the Constitution must be conducted in line with the practice of regional and universal human rights bodies. The author of this paper analyses to which extent the Constitutional Court of Serbia has managed to successfully apply the human rights standards developed in the jurisprudence of the European Court which relate to the principle of non-refoulement with regards to the safe third country concept.